Effect of breathing exercises to prevent pulmonary complications in patients undergoing coronary artery bypass graft surgery: a prospective randomized controlled trials study protocol - Li, Chao; Zhang, Ping; Zhang, Zichang; Qi, Delin; Li, Hongli (Frontiers in Medicine, 2025)
PurposeTo study the effects of breathing exercises on preventing pulmonary complications in patients undergoing coronary artery bypass graft surgery.MethodsObserving whether preoperative breathing exercises can reduce the incidence of postoperative pulmonary complications in patients undergoing coronary artery bypass graft surgery; observing whether these exercises can improve postoperative arterial oxygen pressure, oxygen saturation, and the distance walked in a six-minute walk test after surgery; as well as reduce hospital stay duration, lower treatment costs, and improve the quality of life as measured by the Short Form-36 Health Survey (SF-36).DesignThe study population includes patients undergoing coronary artery bypass graft surgery under general anesthesia; the research center is Capital Medical University Xuanwu Hospital; the sample size is 120. Preoperative standardized breathing exercises are utilized, and the incidence of postoperative pulmonary complications, postoperative arterial blood gases, oxygen saturation, six-minute walk test distances, and comparisons of hospital stay durations and costs will be observed.